ANALISIS PEMANFAATAN TEKNOLOGI INFORMASI DAN KINERJA INDIVIDUAL (STUDI PADA RUMAH SAKIT DI YOGYAKARTA) - ., Sabihaini (Jurnal Widya Manajemen & Akuntansi, 2006)
The aim of this study is to obtain the evidence concerning information technology uses. This paper draws factors that influence information technology uses such as social factor, affect, complexity, job-fit, long-term consequences, facilitating condition; and individual performance in the hospital. The research method used is cluster random sampling method to 120 hospital employees (medic and non medic) shared on three hospitals in Yogyakarta. The Structural Equation Model analysis is used to test the hypothesis. The hypothesis test proved that social factor, complexity, and job-fit, long-term consequences were positively and significantly correlated to information technology uses. Nevertheless, affect and facilitating condition were negatively and not significantly correlated to information technology use. Finally, the last hypothesis test proved that information technology uses was positively and significantly to individual performance as well.